Phase II Randomized Trial of Sequential or Concurrent FOLFOXIRI‐Bevacizumab Versus FOLFOX‐Bevacizumab for Metastatic Colorectal Cancer (STEAM). (14th December 2018) - Hurwitz, Herbert I.; Tan, Benjamin R.; Reeves, James A.; Xiong, Henry; Somer, Brad; Lenz, Heinz‐Josef; Hochster, Howard S.; Scappaticci, Frank; Palma, John F.; Price, Richard; Lee, John J.; Nicholas, Alan; et al.
Abstract: Background: First‐line treatment for metastatic colorectal cancer (mCRC) typically entails a biologic such as bevacizumab (BEV) with 5‐fluorouracil/leucovorin/oxaliplatin (FOLFOX) or 5‐fluorouracil/leucovorin/irinotecan (FOLFIRI). STEAM (NCT01765582) assessed the efficacy of BEV plus FOLFOX/FOLFIRI (FOLFOXIRI), administered concurrently (cFOLFOXIRI‐BEV) or sequentially (sFOLFOXIRI‐BEV, FOLFOX‐BEV alternating with FOLFIRI‐BEV), versus FOLFOX‐BEV for mCRC. Patients and Methods: Patients with previously untreated mCRC ( n = 280) were randomized 1:1:1 to cFOLFOXIRI‐BEV, sFOLFOXIRI‐BEV, or FOLFOX‐BEV and treated with 4–6‐month induction followed by maintenance. Coprimary objectives were overall response rate (ORR; first‐line cFOLFOXIRI‐BEV vs. FOLFOX‐BEV) and progression‐free survival (PFS; pooled first‐line cFOLFOXIRI‐BEV and sFOLFOXIRI‐BEV vs. FOLFOX‐BEV). Secondary/exploratory objectives included overall survival (OS), liver resection rates, biomarker analyses, and safety. Results: ORR was 72.0%, 72.8%, and 62.1% and median PFS was 11.9, 11.4, and 9.5 months with cFOLFOXIRI‐BEV, sFOLFOXIRI‐BEV, and FOLFOX‐BEV, respectively. OS was similar between arms. ORR between cFOLFOXIRI‐BEV and FOLFOX‐BEV did not significantly differ ( p = .132); thus, the primary ORR endpoint was not met. cFOLFOXIRI‐BEV and sFOLFOXIRI‐BEV numerically improved ORR and PFS, regardless of RAS status. Median PFS was higher with pooled concurrent and sequential FOLFOXIRI‐BEV versus FOLFOX‐BEV (11.7 vs. 9.5 months; hazard ratio, 0.7; 90% confidence interval, 0.5–0.9; p < .01). Liver resection rates were 17.2% (cFOLFOXIRI‐BEV), 9.8% (sFOLFOXIRI‐BEV), and 8.4% (FOLFOX‐BEV). Grade ≥ 3 treatment‐emergent adverse events (TEAEs) were observed in 91.2% (cFOLFOXIRI‐BEV), 86.7% (sFOLFOXIRI‐BEV), and 85.6% (FOLFOX‐BEV) of patients, with no increase in serious chemotherapy‐associated TEAEs. Conclusion: cFOLFOXIRI‐BEV and sFOLFOXIRI‐BEV were well tolerated with numerically improved ORR, PFS, and liver resection rates versus FOLFOX‐BEV, supporting triplet chemotherapy plus BEV as a first‐line treatment option for mCRC. Abstract : First‐line treatment for metastatic colorectal cancer is usually a combination of a biologic, such as bevacizumab, with FOLFIRI or FOLFOX; however, these treatments are associated with increased toxicity. This article reports the results of the phase II STEAM trial, which was the largest study of FOLFOXIRI‐BEV in patients in the U.S., comparing the clinical efficacy and tolerability of FOLFOXIRI‐BEV vs FOLFOX‐BEV.